Evaluating the efficacy of LDH and inflammatory indices in discriminating neonatal respiratory distress syndrome from transient tachypnea of the newborns - Hala M. Sakhr; Fayed HM; Amany E. Abdel Aziz; Heba M. Qubaisy (BMC Pediatrics)
Abstract Background Early discrimination between transient tachypnea of the newborn (TTN) and respiratory distress syndrome (RDS) is critical for establishing timely targeted therapies. Our aim was to assess the efficacy of LDH, platelet indices, and systemic inflammatory indices in distinguishing neonatal RDS from TTN early. Methods In total, 300 neonates were enrolled in this case-control study. Lactate dehydrogenase (LDH) levels were estimated. Platelet and systemic inflammatory indices were calculated using complete blood count. Results The RDS group exhibited substantially higher serum levels of LDH, neutrophil-lymphocyte ratio (NLR), and Systemic immune-inflammation index (SII) than the TTN and control groups. Platelet-lymphocyte ratio (PLR) and monocyte-lymphocyte ratio (MLR (were significantly higher in the RDS group than in the TTN group. The RDS group also had the lowest median platelet count, platelet mass index, and WBCs/ mean platelet volume (MPV), but much higher MPV/platelet count than the TTN and control groups. The TTN group had more WBCs, lymphocyte percentage, and count, but a lower neutrophil percentage than the RDS group. The ROC curve study demonstrated that serum LDH at a cut-off level of > 660 U/L can discriminate between the RDS and TTN groups. NLR had the highest sensitivity, PLR had the highest specificity, and SII at a cut-off level > 245.57, had 67% sensitivity and 56% specificity. Significant positive correlations were detected between Downe score with NLR (r = 0.317**, p = 0.001), PLR (r = 0.261**, p = 0.009), and SII (r = 0.270**, p = 0.007). Conclusion LDH levels, platelets, and systematic inflammatory indices could serve as affordable biomarkers for the early distinction between RDS and TTN.